2008
DOI: 10.1089/ten.tec.2007.0359
|View full text |Cite
|
Sign up to set email alerts
|

mRNA Transfection of CXCR4-GFP Fusion—Simply Generated by PCR—Results in Efficient Migration of Primary Human Mesenchymal Stem Cells

Abstract: We present a general, entirely PCR-based strategy to construct mRNAs coding for green fluorescent protein (GFP) fusion proteins from a cDNA pool. We exemplify our approach for the chemokine receptor CXCR4. mRNA transfection of the PCR-generated fusion of CXCR4-GFP into K562 cells or primary mesenchymal stem cells (MSCs) resulted in excellent viability (> 90%) with more than 90% of target cells expressing easily detectable CXCR4-GFP for > 72 h. The fusion protein was localized in the plasma membrane and was rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…To optimize for stability, the mRNA cargo synthesized by in vitro translation was modified through 5= capping with ARCA and by 3= mRNA capping using poly(A) chains in cis and in trans (31). After transfection with ARCA-A100 Luc-mRNA, CD34-derived mouse dendritic cells (JAWSII cells) showed detectable luciferase activity within 1 h, which maximized at 8 h and declined 20-fold at 30 h (31), whereas transfection of primary human mesenchymal stem cells with a CXCR4-GFP fusion mRNA resulted in CXCR4 expression for up to 72 h and in efficient cell migration (32). To increase mRNA stability (33), our constructs included two sequential human beta-globin untranslated regions (UTRs).…”
Section: Discussionmentioning
confidence: 99%
“…To optimize for stability, the mRNA cargo synthesized by in vitro translation was modified through 5= capping with ARCA and by 3= mRNA capping using poly(A) chains in cis and in trans (31). After transfection with ARCA-A100 Luc-mRNA, CD34-derived mouse dendritic cells (JAWSII cells) showed detectable luciferase activity within 1 h, which maximized at 8 h and declined 20-fold at 30 h (31), whereas transfection of primary human mesenchymal stem cells with a CXCR4-GFP fusion mRNA resulted in CXCR4 expression for up to 72 h and in efficient cell migration (32). To increase mRNA stability (33), our constructs included two sequential human beta-globin untranslated regions (UTRs).…”
Section: Discussionmentioning
confidence: 99%
“…Ryser and colleagues reported that electroporation of CXCR4-mRNA resulted in over 90% positively transfected MSCs 36 . However, electroporation disintegrates cell membrane stability with potential side effects and can reduce cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we decided to follow this strategy and engineer MSCs to overexpress the itga4 gene. Since viral-based methods have unfavourable safety profiles and DNA transfection is inefficient, we decided to utilize mRNA which was shown as an effective tool for genetic cell engineering 35, 36 . Since mRNA transfection is an integration-free method, inducing short-lasting expression and high transfection efficiency, it is ideal for the targeted transient induction of itga4 gene expression in MSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it may be the lack of surface expression of CXCR4 by MSC that leads to low efficiency of migration towards CXCL12. This has been further supported by the observation that enforced surface expression of CXCR4 leads to increased MSC engraftment and functional recovery after AMI [49, 69, 70]. Shi et al [65] investigated induced upregulation of CXCR4 in migration of Flk1 + MSC derived from human fetal bone marrow.…”
Section: Role Of Chemokines In Acutely Infarcted Myocardiummentioning
confidence: 97%